MOBILE-BASED DONATION APPLICATION DESIGN AND DEVELOPMENT USING THE SCRUM METHOD - Syaeful Anas Aklani; Daniel Lim (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
In the current era of technology, living standards are increasing, information media can be accessed easily and various technologies are created to facilitate human activities. Almost everyone has decent clothes that they don't use anymore because they don't fit the body or clothes that they don't want to use anymore. People tend to throw away even though the clothes are still worth wearing or keep them even though they are not used. This study discusses the design and development of mobile-based applications. The method used is the Scrum Framework by determining the product backlog, sprint planning, sprint for two weeks, sprint review and sprint retrospective in this study. The result of this research is a mobile-based donation application where donors can donate goods to communities